Factors supporting optimisation of psychotropic deprescribing in people with intellectual disabilities within the UK: a modified Delphi study - Adams, Danielle; Hastings, Richard P.; Maidment, Ian; Langdon, Peter E. (Frontiers in Psychiatry, 2025)
Overprescribing psychotropic medication for people with intellectual disabilities increases the risk of adverse effects and has prompted deprescribing initiatives internationally. However, factors that support optimal psychotropic deprescribing in this population remain unclear. The aim of this study is to develop consensus within the UK about factors supporting optimal psychotropic deprescribing using an online Delphi study. A modified Delphi study with two rounds was distributed via QualtricsXM to a panel of UK healthcare professionals working with people with intellectual disabilities. Thirty-four factors derived from research were presented in round 1 and rated on a 5-point Likert-type scale. Ten factors were presented in round 2 comprising of items not achieving ≥85% consensus in round 1. Participants were able to suggest additional factors in round 1. The key finding was a set of 33 factors supporting optimal psychotropic deprescribing that achieved consensus. Following the round 1 questionnaire, 28 statements reached consensus. Key factors related to attitudes, confidence, conflict resolution, person-centred care, shared decision-making, adherence to guidelines, and mutual learning and support. Following round 2, consensus was reached on five further statements, including two derived from free text responses in round 1. Consensus was reached on 33 factors judged important to promote the safe and effective deprescribing of psychotropic medication for people with intellectual disabilities within the UK. Future practice recommendations should promote equitable and sustainable deprescribing practices informed by experiences of carers and individuals with intellectual disabilities.